Serum stromal cell-derived factor 1α as a prognostic indicator in elderly patients with acute myeloid leukemia receiving CAG-based chemotherapy - Wang, Zhenzhen; Yuan, Jing; Zhou, Nan; Zhang, Jianfeng (Frontiers in Oncology, 2025)
BackgroundStromal-cell-derived factor 1 (SDF-1) plays a crucial role in hematopoiesis and has been implicated in acute myeloid leukemia (AML) pathogenesis. Understanding its relationship with chemotherapy outcomes could lead to improved therapeutic approaches for elderly AML patients.MethodsThis study retrospectively analyzed the medical records of elderly AML patients (n = 187) and compared serum SDF-1α levels with age-matched controls (n = 120). Patients received CAG (cytarabine, aclarubicin, and G‐CSF)-based chemotherapy, and serum SDF-1α levels were assessed using ELISA.ResultsSerum SDF-1α levels were significantly elevated in elderly AML patients compared to controls (p < 0.001). Receiver operating characteristic (ROC) analysis confirmed its diagnostic relevance, revealing the area under the ROC curve (AUC) of 0.76. Factors such as age, French-American-British (FAB) classification, Eastern Cooperative Oncology Group (ECOG) performance status, primary AML status, white blood cell count, and bone marrow blast cell ratio, were confirmed to be prognostically relevant. Serum SDF-1α levels were elevated in patients who did not achieve complete remission (NCR) compared to those in complete remission (CR). ROC analysis further highlighted the predictive capability of serum SDF-1α for chemotherapy responsiveness. Independent predictors of treatment failure included age, FAB classification, ECOG status, and serum SDF-1α levels. Following chemotherapy, serum SDF-1α levels decreased in patients in CR but remained unchanged in those in NCR. Higher baseline levels of SDF-1α were associated with shorter overall survival.ConclusionsElevated serum SDF-1α levels in elderly AML patients are associated with poor chemotherapy response and shorter survival. Baseline serum SDF-1α levels could serve as a prognostic marker for CAG-based treatment outcomes.